The Human Resources Work Concept in Indonesia: A Bibliographic Study of Its Challenges in the Society Era 5.0 - Kusumaningrum, Dyah Ayu Dwi; Fadilla, Dian; Zagladi, Arief Noviarakhman (Business and Investment Review, 2023)
Human resource work in Indonesia is examined in this journal article through the lens of society age 5.0. The difficulties encountered by human resource managers in keeping up with the ever-evolving nature of contemporary society are the subject of an exhaustive bibliographic analysis. To properly manage and develop human capital in Indonesia, this research focuses on a few important areas that need attention and innovation. The research delves into the evolution of human resources in the societal 5.0 era by comparing and contrasting global human resource management principles with the most cutting-edge ideas in the workplace concept.